The Effects of Levetiracetam on the Histological Structure of the Brain and Some Biochemical Parameters in White Male Rats - Shaimaa J.Al Sabaagh, Hanaa E. Mahood, (Pakistan Journal of Medical & Health Sciences, 2022)
The current study aimed to investigate the side effects of Levetiracetam at a dose (25 mg/kg body weight) on brain tissue, as well as the effects of Levetiracetam on liver and renal functions in male white rats. (16) males were used, who were divided into two groups: the first group (control) included eight males, and the second group (treatment) included eight males, who were dosed with drugs throughout the trial period, which amounted to 30 days, after taking blood samples, sacrificing the animals, and making tissue sections of the brain under study. The results revealed that levetiracetam causes a significant increase in hepatic aminotransferases, alkaline phosphatase, renal urea, and creatine when compared to the control at(P≤ 0.05) . The histological study of rat brains in the second group that was treated with Levetiracetam revealed a clear After comparing it to the control group, neurophagia is observed in the brain tissue with clear infiltration of astrocytes and microglia and the presence of edema around blood vessels, as well as degeneration of neuron central, which notes the presence of congestion inside the blood vessel with severe edema. The study concluded that Levetiracetam drugs have effects on the histological of the white rat brain.